The war in Sudan after 2023 and its future prospects: international and political journal - Khalaf, Halah Salim; Muhammad, Khalaf Abdullah (The International and Political Journal, 2024)
This research aims to study the future prospects of war in Sudan after 2023. The research begins by examining the circumstances that led to the emergence and development of this war. The roots of the war witnessed by Sudan go back to distant historical eras, that is, to the period of British colonialism, through the rule of Omar al-Bashir, and ending with the rule of Abdel Fattah al-Burhan. It included a set of different accumulations, the title of which was marginalization, oppression, conflict over power, the creation of tribal loyalties, and greed for the country's economic wealth. This war became intertwined and complicated over time until it produced the current war between the Sudanese army forces and the Rapid Support Forces, which left behind many repercussions, starting from the political level and the accompanying complexity of the scene and the increasing intensity of military polarizations. And passing through the economic level, as the fighting caused the country to enter a stifling economic crisis as a result of the destruction of productive sectors, the flight of foreign investment companies, and the decline in exchange rates. On the humanitarian level, the war left devastating humanitarian effects, such as human rights violations, population displacement, and a lack of basic services in the fields of health and education. Through this research, we will try to formulate a future vision for the war that has been going on in Sudan since 2023, based on the historical approach, the descriptive analytical approach, and the prospective approach required by our future study